Enhancement of Dissolution Rate of Furosemide Using a Solid Dispersion with D-Glucosamine HCl - K. Han, Yong; G. Calvo, Romina; N. Faudone, Sonia; Zitto, Gustavo; Gorzalczany, Susana; Wolfenson, Alberto; Bonafede, Silvina; A. Rosasco, María; I. Segall, Adriana (Current Pharmaceutical Analysis, 2016)
Furosemide is a potent high ceiling (loop) diuretic mainly used in the treatment of edematous states associated with cardiac, renal, and hepatic failure, and the treatment of hypertension. Furosemide has been classified as a class IV drug as per the biopharmaceutical classification system (BCS). D-Glucosamine HCl was used to increase the aqueous solubility of furosemide. The objective of the present work is to improve de dissolution profile of furosemide by formation of a physical mixture and a solid dispersion with D-glucosamine HCl. The solid dispersion was prepared by solvent method using acetone/water. The dissolution properties and physicochemical properties of furosemide: D-glucosamine HCl physical mixture and solid dispersion were investigated by dissolution test, X-ray diffractometry, infrared spectrometry, differential scanning calorimetry (DSC), microscopy (SEM) and 35Cl Nuclear Quadrupole Resonance (NQR). The diuretic activity was proved comparing the solid dispersion with pure furosemide. This study shows that the dissolution rate of furosemide can be enhanced considerably by formulating it with D-glucosamine HCl, as a physical mixture or as a solid dispersion although cristallinity was maintained. Solid dispersion and pure furosemide showed significant increase in diuresis in rats as compared to the control group.
Keywords: diuretic activity